KUALITAS PELAYANAN PUBLIK DALAM MEMBERIKAN KEPUASAN KEPADA MASYARAKAT PADA PELAYANAN SKCK ONLINE POLRES PROBOLINGGO KOTA - Atim Eko Cahyono; Wahyu Endarti; Kodrat Sunyoto (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2023)
The purpose of this study is to analyze the effect of service quality in terms of physical appearance, reliability, responsiveness and empathy on community satisfaction with the online SKCK service innovation of the Probolinggo City Police. This study uses a qualitative approach with a descriptive type of research that aims to provide a detailed and accurate description of the community’s satisfaction with service quality with the research target of service leaders, in this case intelligence officers (Kasat Intelkam), service officers and service users. The results of the study can be seen that the fulfillment of service user community satisfaction in terms of meeting the expectations of service users, the use of service products according to public service standards and ease of access are influenced by the positive response of service users and the application of service standards only, but the quality of human resources (SDM) includes skills, responsiveness and attitudes and behavior of service personnel greatly affect people’s satisfaction.